Perceived Influence of Violent Television Show on Pupil Learning and Academic Performance - Salman, Azeez Arisekola; Adesokan, Adedayo; Ojo, Oluwadamilola Gloria (Bumi Publikasi Nusantara, 2024)
This study examined the perceived influence of violent television shows on pupils' academic performance in the Ilorin West Local Government Area, of Kwara State. The study “adopted a descriptive survey research design, the population comprises of all private and public primary school teachers. The researcher used a simple random sampling technique to select 157 public primary school teachers and 143 private primary school teachers with a total of 300 public and private primary school teachers. One instrument tagged “Questionnaire on Violent Television Show” (QVTS). The reliability coefficient is 0.79. The findings of the study revealed that the level of the perceived influence of violent television shows on pupils' academic performance is very high in Ilorin West Local Government Area, Kwara State, and there was no significant difference in the perceived influence of Violent Television on Pupils Academic Performance based on gender. There was no significant difference in the perceived influence of Violent Television on Pupils' Academic Performance based on school type. it was concluded that the perceived influence of violent television on pupils’ academic performance is very high. It is recommended that parents and guardians should actively monitor and regulate the content their children are exposed to on television, and media literacy in education should be implemented in schools to enhance pupils’ critical thinking skills and ability to analyze and evaluate media content.